Acute effects of blood flow restriction on exercise-induced free radical production in young and healthy subjects - Centner, Christoph; Zdzieblik, Denise; Dressler, Patrick; Fink, Bruno; Gollhofer, Albert; König, Daniel (Free radical research, 2018)
The main purpose of this study was to investigate the acute local and systemic effects of low-load resistance exercise (30% 1RM) with partial vascular occlusion on exercise-induced free radical production and to compare these effects with other established training methods. Fifteen young and healthy males (25 ± 3 years) performed the following four sessions in a counterbalanced order on separate days: low-load resistance exercise (LI: 30% 1RM), low-load resistance exercise with blood flow restriction (LIBR: 30% 1RM), high-load resistance exercise (HI: 80% 1RM) and an additional session without exercise but blood flow restriction only (BR). Blood samples were obtained 15 min prior to and immediately after exercise sessions from the right index finger and first toe. To analyze concentrations of reactive oxygen species (ROS), electron paramagnetic resonance (EPR) spectroscopy was used. Additionally, mitochondrial ROS production was measured by adding inhibitors of electron transport chain complex III. There was an increased systemic ROS generation after the LIBR session from 0.837 ± 0.093 to 0.911 ± 0.099 µmol/l/min. However, no local or systemic time × condition interaction was detected for ROS production. Regarding mitochondrial ROS production, results were not different between the conditions. Although the low-load resistance exercise session with partial vascular occlusion elicited systemic increases of ROS production, no significant changes were seen on a local level. We assume that this ROS concentration might not be high enough to induce cellular damage but is rather involved in muscle remodulation. However, this needs to be confirmed by future research.